ANALYSIS OF SELECTION OF ARSENAL WAREHOUSE LOCATIONS TO SUPPORT KRI OPERATIONS IN THE KOARMADA II AREA ANALYSIS OF ARSENAL STORAGE LOCATION SELECTION TO SUPPORT THE OPERATIONS OF INDONESIAN NAVY WARSHIP (KRI) IN THE 2ND NAVAL FLEET TERRITORY - Muhammad Arif; Budisantoso Wirjodirdjo; I Made Jiwa Astika; Ayip Rivai (JOURNAL ASRO, 2021)
Uncertain global dynamics is one of the main factors influencing the successful achievement of goals and interests in the field of national defense. This reflects how important it is for stakeholders in the defense sector, to understand the dynamics of the strategic environment which presents a series of opportunities, obstacles to threats to the existence of the Republic of Indonesia, which in the end will obtain strategic steps to overcome them. The Indonesian Navy is strongly influenced by several components, such as the strength structure, the level of readiness, the level of sophistication or technological sophistication and the operational durability of its Alutsista. The synergy of the four components of strength is very much determined by the country's ability to build and maintain the ability of the defense equipment. Currently, Arsenal does not have a regional warehouse and there is only one central warehouse in Surabaya. The wide working area of ​​Koarmada II, of course, requires a large number of KRI elements. Arsenal really need regional warehouses in order to be able to increase KRI's operational support in the Koarmada II working area. This is necessary considering that the operation at sea requires a very high presence of KRI. So that if there is a need for ammunition supplies, the process of supplying them can be carried out quickly. This research uses the Fuzzy Multi Criteria Decision Making (FMCDM) method. Overall, the results obtained from this study, it can be concluded that the best location from the alternative location is in the Koarmada II area, namely Lantamal Manado with the highest value of 0. Keywords: Determination of Location, Fuzzy Multi Criteria Decision Making (FMCDM).